Genetic Study of Psoriasis Highlights its Close Link with Socioeconomic Status and Affective Symptoms - Heikkilä, Anni; Sliz, Eeva; Huilaja, Laura; Reis, Kadri; Palta, Priit; Elnahas, Abdelrahman G; Reigo, Anu; Esko, Tõnu; Laisk, Triin; Teder-Laving, Maris; Tasanen, Kaisa; Kettunen, Johannes (Journal of investigative dermatology, 2024)
Psoriasis is an inflammatory skin disease with an estimated heritability of around 70%. Previous GWASs have detected several risk loci for psoriasis. To further improve the understanding of the genetic risk factors impacting the disease, we conducted a discovery GWAS in FinnGen and a subsequent replication and meta-analysis with data from the Estonian Biobank and the UK Biobank; the study sample included 925,649 individuals (22,659 cases and 902,990 controls), the largest sample for psoriasis yet. In addition, we conducted downstream analyses to find out more about psoriasis' cross-trait genetic correlations and causal relationships. We report 6 risk loci, which, to our knowledge, are previously unreported, most of which harbor genes related to NF-κB signaling pathway and overall immunity. Genetic correlations highlight the relationship between psoriasis and smoking, higher body weight, and lower education level. In addition, we report causal relationships between psoriasis and mood symptoms as well as 2-directioned causal relationship between psoriasis and lower education level. Our results provide further knowledge on psoriasis risk factors, which may be useful in the development of future treatment strategies.